PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TEAM GAMES TOURNAMENTS) UNTUK MENINGKATKAN KEAKTIFAN DAN KETUNTASAN BELAJAR SISWA PADA POKOK BAHASAN SISTEM KOLOID DI KELAS XII TKJ SMK YAPIM SIAK HULU: (Cooperative Learning Model Application TGT Type (Team Games Tournaments) to Increase Activity and Students’ Complete Learning on Colloid Systems at Class XII TKJ SMK YAPIM Siak Hulu) - Rosa Murwindra (Perspektif Pendidikan dan Keguruan, 2017)
The research was classroom action research (CAR). The purpose was to improved student’s activeness and mastery of chemistry learning which concerned to colloid systems by using cooperative learning model type TGT (team games tournaments) at the XII grade of engineering major (TKJ) in SMK YAPIM Siak Hulu, district of Kampar, RIAU. Based on the result of research which accomplished into two cycles, I cycle and II cycle by applying cooperative learning model, particularly TGT (team games tournaments) type during chemistry teaching learning process could improve student’s activeness and score completeness of chemist learning the average presentation of students activity in I cycle was 54,59% (enough), meanwhile in II cycle was 63,52% (enough). The improvement of students learning activity presentation was followed by the improvement of students accomplishment in chemist learning at I cycle as 77,42% (STDS) and II cycle as 87,10% (STDS.).